Nekateri izbrani vidiki prakse s področja diplomatskega in konzularnega prava v Sloveniji - Sancin, Vasilka (Teorija in praksa, 2011)
As a sovereign state, in its interaction with other subjects of international law, Slovenia respects and implements the rules and principles of diplomatic and consular law. Following the dissolution of the former SFRY it succeeded to all the core treaties of diplomatic and consular law and adopted relevant domestic legislation. In addition to the Slovenian Constitution, the Foreign Affairs Act and regulations adopted within the Ministry of Foreign Affairs hold central importance. After nearly two decades of theory and practice of diplomatic and consular law in Slovenia, this article offers an overview of some basic features of this development, with a particular emphasis on individual selected aspects, including new developments in the area of consular assistance offered to EU citizens by EU member states in third countries, as this assistance has proven to be very important for Slovenian nationals in practice. When assessing each selected topic some conclusions and proposals for the future regulation of these issues are presented.
Keywords: Diplomatic law; Diplomatsko pravo; Konzularno pravo; Consular law; Slovenia; Slovenija; mednarodno pravo